Laparoscopic Ist stage orchiopexy using antiadherent sheet for high abdominal testis - D. Falchetti; L. Corasaniti; M. Lanata; S. Argento; M. Pellegrino; A. Dessanti (Elsevier, 2020)
High undescended testes with short spermatic vessels are not treated with standard orchiopexy and are currently brought to scrotum prevalently after the section of spermatic vessels, according to the Fowler-Stephens procedure. The ischemic risk of that method is elevated and becomes unbearable in bilateral cases.In 2009 an original staged orchiopexy technique was proposed to elongate the whole cord with anti-adherent sheet preserving the spermatic vessels by which a normal scrotal position was successfully gained without any testis loss. Both stages were performed through inguinotomy.In the present article the successful procedure is updated with implementation of laparoscopy in the first stage in a case of extremely high bilateral 4a type abdominal testis.Laparoscopic access was confirmed as valuable both in terms of extended mobilization and coverage of the entire testis vascular supply.The method of progressive cord elongation by using an anti-adherent sheet avoids the excessive atrophy hazard deriving from the Fowler-Stephens procedure in bilateral high abdominal 4a type testes; based on our findings, the latter can benefit also of a laparoscopic approach in the first stage.